Masting in wind‐pollinated trees: system‐specific roles of weather and pollination dynamics in driving seed production. Issue 10 (22nd August 2017) - Bogdziewicz, Michał; Szymkowiak, Jakub; Kasprzyk, Idalia; Grewling, Łukasz; Borowski, Zbigniew; Borycka, Katarzyna; Kantorowicz, Władysław; Myszkowska, Dorota; Piotrowicz, Katarzyna; Ziemianin, Monika; Pesendorfer, Mario B.
Abstract: Masting, the highly variable production of synchronized large seed crops, is a common reproductive strategy in plant populations. In wind‐pollinated trees, flowering and pollination dynamics are hypothesized to provide the mechanistic link for the well‐known relationship between weather and population‐level seed production. Several hypotheses make predictions about the effect of weather on annual pollination success. The pollen coupling hypothesis predicts that weather and plant resources drive the flowering effort of trees, which directly translates into the size of seed crops through efficient pollination. In contrast, the pollination Moran effect hypothesis predicts that weather affects pollination efficiency, leading to occasional bumper crops. Furthermore, the recently formulated phenology synchrony hypothesis predicts that Moran effects can arise because of weather effects on flowering synchrony, which, in turn, drives pollination efficiency. We investigated the relationship between weather, airborne pollen, and seed production in common European trees, two oak species ( Quercus petraea and Q. robur ) and beech ( Fagus sylvatica ) with a 19‐yr data set from three sites in Poland. Our results show that warm summers preceding flowering correlated with high pollen abundance and warm springs resulted in short pollen seasons (i.e., high flowering synchrony) for all three species. Pollen abundance was the best predictor for seed crops in beech, as predicted under pollen coupling. In oaks, short pollen seasons, rather than pollen abundance, correlated with large seed crops, providing support for the pollination Moran effect and phenology synchrony hypotheses. Fundamentally different mechanisms may therefore drive masting in species of the family Fagacae.